Epidermal Structure of some Important Forest Plants 4. Sapindus - Farooqui, Parveen; Venkatasubramanian, N. (Indian Forester, 1986)
A comparative study of the epidermal characters of SapinduS emarginata and s. laurifolia has been made. It is found that the two species can easily be distinguished on the basis of the above characters.